Soybean cyst nematode culture collections and field populations from North Carolina and Missouri reveal high incidences of infection by viruses - Ruark, Casey L. (PLoS One, 2017)
Five viruses were previously discovered infecting soybean cyst nematodes (SCN; Heterodera glycines) from greenhouse cultures maintained in Illinois. In this study, the five viruses [ScNV, ScPV, ScRV, ScTV, and SbCNV-5] were detected within SCN greenhouse and field populations from North Carolina (NC) and Missouri (MO). The prevalence and titers of viruses in SCN from 43 greenhouse cultures and 25 field populations were analyzed using qRT-PCR. Viral titers within SCN greenhouse cultures were similar throughout juvenile development, and the presence of viral anti-genomic RNAs within egg, second-stage juvenile (J2), and pooled J3 and J4 stages suggests active viral replication within the nematode. Viruses were found at similar or lower levels within field populations of SCN compared with greenhouse cultures of North Carolina populations. Five greenhouse cultures harbored all five known viruses whereas in most populations a mixture of fewer viruses was detected. In contrast, three greenhouse cultures of similar descent to one another did not possess any detectable viruses and primarily differed in location of the cultures (NC versus MO). Several of these SCN viruses were also detected in Heterodera trifolii (clover cyst) and Heterodera schachtii (beet cyst), but not the other cyst, root-knot, or reniform nematode species tested. Viruses were not detected within soybean host plant tissue. If nematode infection with viruses is truly more common than first considered, the potential influence on nematode biology, pathogenicity, ecology, and control warrants continued investigation.